Association between pulse wave velocity and the 10‐year risk of atherosclerotic cardiovascular disease in the Chinese population: A community‐based study. Issue 3 (15th February 2023) - Yi, Tieci; Gao, Lan; Fan, Fangfang; Jiang, Yimeng; Jia, Jia; Zhang, Yan; Li, Jianping; Huo, Yong
Abstract: Accumulated evidence has shown that carotid‐femoral and brachial‐ankle PWV well predict cardiovascular events but it is still unclear if the predictability is same or not. In this cross‐sectional study based on a community atherosclerosis cohort in Beijing, China, a total of 5282 participants without previous coronary heart disease and stroke were enrolled from a community atherosclerosis cohort in Beijing, China. The 10‐year atherosclerotic cardiovascular disease (ASCVD) risk were calculated by the China‐PAR model, and < 5%, 5%–10% and > 10% were defined as low, intermediate, and high risk, respectively. The average baPWV and cfPWV values were 16.63 ± 3.35 m/s and 8.45 ± 1.78 m/s, respectively. The mean 10‐year ASCVD risk was 6.98% (interquartile range: 3.90%–12.01%). The patients with low, intermediate, and high 10‐year ASCVD risk accounted for 34.84% (1840), 31.94% (1687), , and 33.23% (1755) respectively. Multivariate analysis showed that for every 1 m/s increase in baPWV and cfPWV, the 10‐year ASCVD risk increased by 0.60% (95% confidence interval: 0.56%–0.65%, p  < .001) and 1.17% (95% confidence interval: 1.09%–1.25%, p  < .001), respectively. The diagnostic ability of the baPWV was comparable to the cfPWV (area under the curve: 0.870 [0.860–0.879] vs. 0.871 [0.861–0.881], p  = .497). In conclusion, baPWV and cfPWV are positively associated with the 10‐year risk of ASCVD in the Chinese community‐based population, with a nearly identical association with a high 10‐year risk of ASCVD.